Enhancing the therapeutic activity of hyperimmune IgG against chikungunya virus using FcγRIIIa affinity chromatography - Fox, Julie M.; Roy, Vicky; Gunn, Bronwyn M.; Bolton, Glen R.; Fremont, Daved H.; Alter, Galit; Diamond, Michael S.; Boesch, Austin W. (Frontiers in Immunology, 2023)
Chikungunya virus (CHIKV) is a re-emerging mosquito transmitted alphavirus of global concern. Neutralizing antibodies have been shown to reduce CHIKV disease and infection in animals. Importantly, antibody Fc-effector functions are necessary for optimal monoclonal antibody therapeutic activity against CHIKV. However, the ability to improve the therapeutic activity of CHIKV-specific polyclonal IgG by enhancing Fc-effector functions through modulation of IgG subclass and glycoforms remains unknown. Here, we evaluated the protective efficacy of total IgG isolated from CHIKV-immune convalescent donors with and without purification by Fc-gamma receptor IIIa (FcγRIIIa) affinity chromatography to enrich for IgG with enhanced Fc effector functions. FcγRIIIa-column purification enriched for afucosylated IgG glycoforms. In vitro characterization showed the enriched CHIKV-immune IgG had enhanced human FcγRIIIa and mouse FcγRIV affinity and FcγR-mediated effector function without reducing virus neutralization in cellular assays. When administered as post-exposure therapy in mice, CHIKV-immune IgG enriched in afucosylated glycoforms promoted reduction in viral load. Overall, our study provides evidence that in mice, increasing Fc engagement of FcγRs on effector cells, by leveraging FcγRIIIa-affinity chromatography, enhanced the antiviral activity of CHIKV-immune IgG and reveals a path to produce more effective therapeutics against these and potentially other emerging viruses.